If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10x + -6 = -26 Reorder the terms: -6 + -10x = -26 Solving -6 + -10x = -26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -10x = -26 + 6 Combine like terms: -6 + 6 = 0 0 + -10x = -26 + 6 -10x = -26 + 6 Combine like terms: -26 + 6 = -20 -10x = -20 Divide each side by '-10'. x = 2 Simplifying x = 2
| 8X-3=40X+5 | | 8(3)=3(8.1) | | 10x-2x=24 | | (8.1)+8.1(3)=0 | | -5+6y=69 | | -13=1+2p-6 | | -7/8=m-3/8 | | -3(2+x)+4x=6x-5(1+x)+11 | | 10(8.1)=27(3) | | 3x+83=71 | | 1872*18=x | | -18x+9y=54 | | 4(8.1)-10(3)=0 | | -k+5+6k=10 | | 6-2x=5x-9+10-4 | | 6=3x-12 | | -12x+4y=-4 | | 81v^2-180vd+100d^2=0 | | g(x)=(3x-4)-(-6+4x) | | 6-3x=6x-10x+8-2 | | 8x=3y | | w/4+3=7 | | (x+4)-7=x | | 60-3x=150 | | 2(2x+7)=42 | | 20x-8-14x+2=18x-9-12x+13 | | 9x+5y=82 | | x^2=4-3x | | 9-22.5=x | | 9x-13y=94 | | 7.25=2*3.14r | | x^2+6x-12=0 |